Bacterial Etiology and Serotype Distribution of Streptococcus Pneumoniae in Acute Respiratory Infections among Displaced Rohingya Population Settled in Humanitarian Refugee Camps of Cox’s Bazar, Bangladesh (IAHS Medical Journal, 2026)
Background: Morbidity and mortality are a common cause of Acute Respiratory Infections (ARIs)in refugee populations. This study was carried out to examine the bacterial etiology and track the distribution patterns of Streptococcus pneumoniae serotype among the Displaced Rohingya Population (DRP) in Cox’s Bazar, Bangladesh.Materials and methods: It was a prospective case-control study of ARI conducted among the DRP. A total of 538 nasopharyngeal samples (NPS) of ARI cases were enrolled according to WHO criteria and also enrolled age-sex matched 514 controls in the Displaced Rohingya Population (DRP) settled in refugee camps in Cox’s Bazar, Bangladesh, between June 2018 to March 2020.Results: The study data showed that in both the ARI cases and control group, children £ 5 years of age had a higher bacterial positivity (90%) than those >5 years of age.S. pneumonia was found predominantly in both cases and controls (77% and 78%). In the serotype distribution pattern of S.pneumoniae, 6AB (12.8%), 23F (9.3%), 15B/C (8.3%), 19A (8.07%), 11A (7.3%), 35B (7.1%), 13 (6.08%), 34 (5.3%) serotypes were found in greater proportions which covered 64.25% of all isolates and 1, 21, 19F, 2, 4, 33F, 39, 8 serotypes were found in less proportions.Conclusion: Overall, these comprehensive data on the specific causes and findings related to the health situation, especially in crisis contexts such as the Rohingya refugees in Cox's Bazar, Bangladesh are vital for effective disease management, prevention control and vaccination strategies in humanitarian crisis.IAHS Medical Journal Vol 8(1), June 2025; 7-16